Give Full Play to The Linkage and Resonance Role Between the Shenyang Metropolitan Area And The China-Japan-ROK Free Trade Zone - Jiang, Xin (Economics & Management Review, 2023)
The connection between civil servants and the public is the closest, and their service to the public is the most direct. Every major government policy is ultimately implemented and carried out by civil servants. However, under the influence of multiple factors, the enthusiasm of some civil servants is gradually diminishing. This article conducts interviews and analyzes questionnaire data from civil servants in different regions. Combined with demand theory, two-factor theory, and equity theory, the surveyed data is discussed and analyzed. The study demonstrates the existing problems and advantages of the current incentive policies for civil servants in China